2019
DOI: 10.1029/2019jd030622
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Edge Properties Measured by the ARM Shortwave Spectrometer Over Ocean and Land

Abstract: We use the spectrally invariant method to study the variability of cloud optical thickness (τ) and droplet effective radius (r eff ) in transition zones between the cloudy and clear-sky columns observed by Shortwave Array Spectroradiometer-Zenith at the Southern Great Plains Central Facility site (SGP C1) and during the Marine ARM GPCI Investigation of Clouds (MAGIC) field campaign. The spectrally invariant method approximates the spectra in the transition zone as a linear combination of definitely clear an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…When applying this method to the measurements of a ground-based shortwave spectroradiometer in continental and maritime conditions (Yang et al, 2016(Yang et al, , 2019, we found that cloud optical depth consistently decreases in both cases, while droplet size decreases much more substantially for the continental regime, suggesting different mixing processes for the two types of clouds. This is consistent with our theoretical understanding of the effect of relative humidity on the mixing types (Pinsky and Khain, 2018).…”
Section: Observing Mixing and Aerosol-cloud Interactions In The Transmentioning
confidence: 97%
See 1 more Smart Citation
“…When applying this method to the measurements of a ground-based shortwave spectroradiometer in continental and maritime conditions (Yang et al, 2016(Yang et al, , 2019, we found that cloud optical depth consistently decreases in both cases, while droplet size decreases much more substantially for the continental regime, suggesting different mixing processes for the two types of clouds. This is consistent with our theoretical understanding of the effect of relative humidity on the mixing types (Pinsky and Khain, 2018).…”
Section: Observing Mixing and Aerosol-cloud Interactions In The Transmentioning
confidence: 97%
“…McBride et al 2011) or the shape (LeBlanc et al 2015) of the SW spectra mitigate challenges with absolute calibration accuracy allowing more effective use of the spectral measurements. For example, the studies of the mixing zone between clear and cloudy skies described in the following section use retrievals of cloud optical depth and effective radius from multiple spectral zenith radiance instruments with absolute accuracy differences of 15-20%, but these accuracy differences had little impact on the retrievals because ratios of cloudy and clear spectra are used (Yang et al, 2016(Yang et al, , 2019; Section S5).…”
mentioning
confidence: 99%